A randomized trial on the effects of CitrusiM® (Citrus sinensis (L.) Osbeck dried extract) on body composition. (October 2019) - Kegele, Carolina Schettino; Oliveira, Julia; Magrani, Taiana; Ferreira, Aline; de Souza Ferreira, Raquel; Sabbaghi, Arman; de Oliveira Ferreira, Anderson; Brandão, Marcos Antônio Fernandes; Raposo, Nádia Rezende Barbosa; Polonini, Hudson Caetano
Summary: Objective: In this report, we investigated the effects of CitrusiM® ( Citrus sinensis (L.) Osbeck dried extract) on body composition, defined in terms of two outcomes: percentage of lean mass and percentage of fat mass. Research methods & procedures: A double-blind randomized experiment with overweight and obese volunteers was conducted in which the two variables were measured at baseline and three months afterwards. The treatment levels corresponded to three different daily doses of CitrusiM®: 0 mg (control), 0.5 g, and 1 g. All patients met with a nutritionist, and were given a standardized diet with their assigned treatments. At the end of three months, the intermediate outcomes of diet compliance (in percent) and amount of exercise (either none, low level, or high level) were recorded. The covariates that were collected for each subject were age, height, and sex. We analyzed the effects of the treatments on the two outcomes under a Bayesian framework of the Rubin Causal Model, and accounted for possible relationships between both diet compliance and exercise level and the three outcomes of interest in the analyses. Study registered under Research Ethics Committee of the Faculdade de Ciências Médicas e da Saúde de Juiz de For a (plataformabrasil.gov.br): Identifier no. 2.767.611. Results: There was a statistically significant evidence that the treatment may increase lean mass and reduce fat mass. Conclusion: A 3-month treatment with CitrusiM® (0.5 g or 1 g, daily) was able to increase lean mass, reduce fat mass, in the participants.